Trajetórias acadêmicas de estudantes de psicologia - Lobo, Adria Nadine de Moraes (Brasil, 2024)
The academic paths in a college degree is marked by challenges of entry and staying in the university. In this context, a psychology degree demands dedication from the student because it equips them for professional practice with mastery of psychological theories and techniques, along with ethical conduct. This educational scenario is challenging and can be compounded by the students' own difficulties in staying at the university. The study design was qualitative, characterized as a cross-sectional and descriptive study based on narrative interviews with two undergraduate psychology students. The interviews were analyzed using Thematic Analysis, which allowed for an understanding of various events and moments in the students' education. The results demonstrate that the major difficulties identified for staying in and completing the degree were economic challenges, social inequalities experienced at the university, expectations about the course, and as support, they found their families and peers. This study enabled an understanding of academic paths in the college of psychology education and may assist in the development of actions aimed at better supporting students in the program.